Creation of a Human Factors Board to Support Well-Being in General Surgery Residents. (19th July 2022) - McLaughlin, Christopher J.; Stahl, Kelly A.; Allen, Steven R.; Dodge, Daleela G.
Abstract : Problem: Demands placed on resident physicians can make it difficult to keep up with personal needs, often affecting well-being. For military pilots, confidential and nonpunitive human factors boards (HFBs) identify pilots' human factors (personal or professional problems that might interfere with the ability to perform effectively) and make recommendations for support. The authors sought to determine the feasibility of establishing an HFB for resident physicians and its utility for general surgery residents. Approach: Publicly available information on HFBs was reviewed and translated to the structure of a general surgery residency. An HFB consisting of a faculty member, resident representative, and neutral third party was established for the general surgery residency program (consisting of 42 residents during the study period) at Penn State Health. From January 1 to July 1, 2020, the HFB responded to human factors needs of general surgery residents. Residents could make requests for themselves or another resident. If all HFB members were in agreement that a request was reasonable, the appropriate resource was directed to the requesting resident and funding was disbursed (if applicable) by the third party. Outcomes: From January 1 to July 1, 2020, 14 requests were made. Of these, 3 (21%) were made for another resident and 12 (86%) were fulfilled through resources arranged by the HFB. All requests occurred between January 1 and April 1, 2020, likely because of the COVID-19 pandemic. The overall cost of the program was $932.80. Next Steps: The HFB represents an adaptable tool that can meet residents' specific needs as they arise and a mechanism through which residents can receive a tangible response to human factors. Formal feedback is needed to identify areas that could be improved. This structure could be generalized to other graduate medical education programs and physicians at all levels.